Integrated transcriptomics and physio-biochemical analysis revealed key genes affecting the seed germination of Leymus chinensis - Feng, Yumei; Gong, Wenlong; Liu, Lemeng; Tian, Chunyu; Yang, Yanting; Wu, Zinian (Frontiers in Plant Science, 2025)
Leymus chinensis, also known as alkali grass, is a perennial rhizomatous herbaceous plant with a significant ecological and economic value. However, its industrial development is hindered by low seed germination rates. Therefore, how to break the seed dormancy and improve the germination rate of L. chinensis seeds has become a hot topic nowadays. In this study, the increase of gibberellin (GA) content is one of the main factors promoting the seed germination of L. chinensis. Furthermore, to further explore the molecular mechanisms underlying seed germination regulation, RNA sequencing (RNA-seq) analysis of seeds at different developmental stages was carried out to explore the potential regulatory factors of seed hulls affecting the seed germination of L. chinensis. A total of 21,564, 21,010, and 31,795 differentially expressed genes (DEGs) were identified in “H_CK_0 vs. DH_CK_0”, “H_CK_2 vs. DH_CK_2”, and “H_CK_7 vs. DH_CK_7”, respectively. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis showed that the DEGs were significantly enriched in plant hormone signal transduction, starch and sucrose metabolism, and mitogen-activated protein kinase (MAPK) signaling pathways. Within these pathways, we identified several candidate genes potentially involved in seed hull-mediated germination regulation, including those encoding α-amylase (AMY1), β-amylase (BAM1), α-xylosidase (XYL1), β-glucosidase (BGLU10/45), auxin-responsive protein (IAA18), and transcription factors (WRKY, AP2/ERF, ABI2, bZIP, and NAC). These results provide valuable genetic resources for studying the molecular mechanism of L. chinensis seed germination.